YouTube Sebagai Arena Produksi dan Reproduksi Kultur Hip-Hop - Edra Ramadhan Praliansyah (Antropologi Indonesia, 2021)
This article discusses the so-called YouTube rapper phenomenon, a new subgenre of hip-hop music whose emergence was caused by YouTube. Rap or hip-hop, which has a long history of intergroup resistance from stage to stage, has now moved to YouTube as a new battleground, producing the YouTube rapper subgenre. This article shows that the hip-hop community was very responsive to YouTube, which was their new stage, alongside Discord and Facebook as more textual media employable for debate and discussion. This article argues that YouTube has the capacity to become a center of hip-hop capitalization in Indonesia, as in elsewhere, because it was proven to be able to produce and reproduce the culture of hip-hop.